2020
DOI: 10.1525/elementa.420
|View full text |Cite
|
Sign up to set email alerts
|

Multi-decadal surface ozone trends at globally distributed remote locations

Abstract: Extracting globally representative trend information from lower tropospheric ozone observations is extremely difficult due to the highly variable distribution and interannual variability of ozone, and the ongoing shift of ozone precursor emissions from high latitudes to low latitudes. Here we report surface ozone trends at 27 globally distributed remote locations (20 in the Northern Hemisphere, 7 in the Southern Hemisphere), focusing on continuous time series that extend from the present back to at least 1995.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
111
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(130 citation statements)
references
References 141 publications
(236 reference statements)
18
111
1
Order By: Relevance
“…Petetin et al (2018) validated IAGOS data in the lowest troposphere over western Europe against rural monitoring sites at various elevations and concluded that those observations can be used to study the air quality in the agglomeration. Nevertheless, to reduce the influence from the strong diurnal cycle at the surface, all observations below the 950 hPa level and within 300 m of the surface were removed from the analysis (Gaudel et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Petetin et al (2018) validated IAGOS data in the lowest troposphere over western Europe against rural monitoring sites at various elevations and concluded that those observations can be used to study the air quality in the agglomeration. Nevertheless, to reduce the influence from the strong diurnal cycle at the surface, all observations below the 950 hPa level and within 300 m of the surface were removed from the analysis (Gaudel et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The O3 monthly anomalies are more precise than O3 monthly means because of the reducing impact of missing data. Using this method, Cooper et al (2020) and Lu et al (2020) quantified the O3 trend in 27 globally distributed remote locations and the whole China. In addition, anomalies of monthly average O3 concentration are defined as the difference between the individual monthly mean and the monthly mean of 2014-2018.…”
Section: Linear Trend Analysesmentioning
confidence: 99%
“…Concentrations of ground-level ozone (O 3 ) have increased throughout the northern hemisphere since the industrial revolution [ 1 , 2 , 3 , 4 ]. Urban, suburban, rural, and remote areas are generally exposed to elevated O 3 levels, in terms of both average and maximum concentrations, and mathematical models suggest that this environmental issue may persist over several coming decades [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations of ground-level ozone (O 3 ) have increased throughout the northern hemisphere since the industrial revolution [ 1 , 2 , 3 , 4 ]. Urban, suburban, rural, and remote areas are generally exposed to elevated O 3 levels, in terms of both average and maximum concentrations, and mathematical models suggest that this environmental issue may persist over several coming decades [ 1 , 2 , 3 , 4 ]. Moreover, an analysis of air quality following the lockdown imposed in global cities during the COVID-19 pandemic revealed a considerably amplified O 3 pollution in cities [ 5 ], highlighting the complexity of this environmental issue and the difficulty to reduce O 3 pollution [ 5 ].…”
Section: Introductionmentioning
confidence: 99%